1999
DOI: 10.1007/bf03401992
|View full text |Cite
|
Sign up to set email alerts
|

CXC and CC Chemokine Receptors on Coronary and Brain Endothelia

Abstract: Background: Chemokine receptors on leukocytes play a key role in inflammation and HIV-1 infection. Chemokine receptors on endothelia may serve an important role in HIV-1 tissue invasion and angiogenesis. Materials and Methods: The expression of chemokine receptors in human brain microvascular endothelial cells (BMVEC) and coronary artery endothelial cells (CAEC) in vitro and cryostat sections of the heart tissue was determined by light and confocal microscopy and flow cytometry with monodonal antibodies. Chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 44 publications
6
90
0
1
Order By: Relevance
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 97%
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 97%
“…MCP-1 is induced by various stimuli, such as cytokines and oxidized adducts, and is secreted from endothelial cells, smooth muscle cells and macrophages (Myers et al, 1996). CC chemokine receptor (CCR) 2 is highly expressed in peripheral blood monocytes, macrophages, and T lymphocytes and it is the only established functional receptor for MCP-1 on hematopoietic cells (Boring et al, 1998;Berger et al, 1999;Han et al, 2000). Although MCP-1 and CCR2 are believed to play an important role in leukocyte trafficking and the development of atherosclerosis, little information is available regarding the mechanism of intracellular signaling events that regulates the expression of chemokine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…CCR5 is expressed on a number of hematopoietic cells, including lymphocytes, macrophages, and granulocytes, and also on non-hematopoietic cells [15][16][17][18]. CCR5 binds to multiple chemokines including CCL3, CCL4/ MIP-1b, and CCL5 [19,20].…”
Section: Introductionmentioning
confidence: 99%